Peroxisomes Regulate Cellular Free Fatty Acids to Modulate Mast Cell TLR2, TLR4, and IgE-Mediated Activation - Meghnem, Dihia; Leong, Edwin; Pinelli, Marinella; Marshall, Jean S.; Di Cara, Francesca (Frontiers in Cell and Developmental Biology, 2022)
Mast cells are specialized, tissue resident, immune effector cells able to respond to a wide range of stimuli. MCs are involved in the regulation of a variety of physiological functions, including vasodilation, angiogenesis and pathogen elimination. In addition, MCs recruit and regulate the functions of many immune cells such as dendritic cells, macrophages, T cells, B cells and eosinophils through their selective production of multiple cytokines and chemokines. MCs generate and release multi-potent molecules, such as histamine, proteases, prostanoids, leukotrienes, heparin, and many cytokines, chemokines, and growth factors through both degranulation dependent and independent pathways. Recent studies suggested that metabolic shifts dictate the activation and granule content secretion by MCs, however the metabolic signaling promoting these events is at its infancy. Lipid metabolism is recognized as a pivotal immunometabolic regulator during immune cell activation. Peroxisomes are organelles found across all eukaryotes, with a pivotal role in lipid metabolism and the detoxification of reactive oxygen species. Peroxisomes are one of the emerging axes in immunometabolism. Here we identified the peroxisome as an essential player in MCs activation. We determined that that lack of functional peroxisomes in murine MCs causes a significant reduction of interleukin-6, Tumor necrosis factor and InterleukinL-13 following immunoglobulin IgE-mediated and Toll like receptor 2 and 4 activation compared to the Wild type (WT) BMMCs. We linked these defects in cytokine release to defects in free fatty acids homeostasis. In conclusion, our study identified the importance of peroxisomal fatty acids homeostasis in regulating mast cell-mediated immune functions.